An investigation into stylistic devices used in business English speeches delivered in Ted conferences - Phạm,Hà Mỹ Hạnh; Lưu Quý Khương (ĐHĐN : ĐHĐN., 2015)
This thesis examined stylistic devices used in businees speeches delivered in Ted conferences. The data of the study were collected from business speeches in Ted conferences. The data was described and analyzed on stylistic aspects under qualitative and quantitative approaches to yield more precise points on stylistic devices in English business speeches in Ted conferences. On a close analysis, the thesis tried to find out some commonly used stylistic devices in business language in English business speeches, namely repetition, metonymy, metaphor, rhetorical questions, alliteration, and personification and to find out the function of stylistic devices in business speeches. With the hope of contributing to better teaching and learning English as a foreign language, especially to better the awareness of learners in understanding and writing a persuasive and interesting speech, some suggested ideas were also included.
Keywords: stylistic devices used in business English speeches delivered in Ted conferences; stylistic devices -- business English